On the tail risk premium in the oil market - Reinhard Ellwanger (Bank of Canada, 2017)
This paper shows that changes in market participants' fear of rare events implied by crude oil options contribute to oil price volatility and oil return predictability. Using 25 years of historical data, we document economically large tail risk premia that vary substantially over time and significantly forecast crude oil futures and spot returns. Oil futures prices increase (decrease) in the presence of upside (downside) fears in order to allow for smaller (larger) returns thereafter. This increase (decrease) is amplified for the spot price because of time varying-benefits from holding physical oil inventories that work in the same direction. We also provide support for view that that time variation in the relative importance of oil demand and supply shocks is an important determinant of oil price fluctuations and their interaction with aggregate outcomes. However, the option-implied tail risk premia are not spanned by traditional macroeconomic and oil market uncertainty measures, suggesting that time-varying oil price fears are an additional source of oil price volatility and predictability.
Keywords: C53; C58; D84; E44; G12; G13; Q43; 330; Asset pricing; Econometric and statistical methods; Financial markets